The misconceptions of religious pluralism and religious plurality held by muslims in Malaysia - Idris, Fathiyyatunnur; Farid Ali, Mohammed (IKIM, 2022)
This paper reviews the concepts of religious pluralism and religious plurality in works written by both Western and Muslim scholars. Religious pluralism in the West, its causes of origin, differences in opinion amongst Western scholars, and its influence on the Muslim world are presented. The paper finds that in Muslim countries such as Malaysia, there are people who propagate religious pluralism and there are people who oppose it completely. Between those who propagate and those who oppose, there are also those who partially understand or completely do not understand at all the philosophy of religious pluralism. There are some scholars, however, who agree with religious plurality (diversity), but they are often mistaken by others who are not familiar with the subtle differences between “pluralism” and “plurality.”